Development and characterization of targeted mart-1-nanoparticles for melanoma treatment and β-lapachone-loaded liposomes in hydrogel for wound healing - PALÁCIO, Sarah Brandão (2017)
The main aim of this work was the development, characterization and in vitro and in vivo evaluation of different nanocarriers with specific nanoparticles for the treatment of melanoma and β-lapachone liposomes incorporated in biopolymer hydrogels for the healing of topical wounds. The first part of this thesis presents a review of the literature and recent advances in the field of targeting mesenchymal circulating cells derived from melanomas. The main biomarkers of these cells have been reviewed to define the suitable characteristics of this nanocarriers. The experimental part of the work consisted of development of nanoparticles (non-spherical) by nanoprecipitation of copolymers derived from poly (γ-benzyl-L-glutamate). These nanoparticles, size between 20 and 100 nm and carrying a negative charge (-3 to -30 mV) were then combined with the MART-1 antibody, specific for the melanoma cell membrane, by biotin-streptavidin binding. The binding of the antibody on the surface of nanoparticles was evaluated by Western blot. The affinity of immuno-nanoparticles for melanoma cells (B16-GFP line) and for endothelial cells of human umbilical vein (HUVECs) was then evaluated in vitro by flow cytometry and, being intended for intravenous injection, it was important to evaluate the degree of activation of the complement system induced by the nanoparticles. The 2D immunoelectrophoresis technique used made it possible to conclude that the activation was limited and favourable to increase the blood circulation time of nanoparticles, after intravenous injection. The nanoparticles exhibited low cytotoxicity (MTT assay) against melanoma cells or endothelial cells. In terms of cellular uptake, the immuno-nanoparticles functionalized with MART1, a specific antibody for the recognition of the overexpressed antigen in melanoma cells, was increased by 40 to 50% compared to control. The second part of this thesis was dedicated to the development, characterization and in vivo evaluation of the wound healing activity of β-lapachone encapsulated in multilamellar liposomes and incorporated in a hydrogel of a biopolymer produced by the bacterium Zoogloea sp. These original formulations (β-lap-Lipo/ ZBP/HEC) had a pH and rheological behavior suitable for topical application, as well as the ability to slow the release of β-lapachone from the hydrogel. A detailed histopathological study of the wound healing activity was conducted in an in vivo model and showed that the biopolymer hydrogel was able to stimulate tissue repair, increasing the local cellularity, fibroblasts, cells inflammatory, blood vessels and the production of collagen fibrils during the proliferative phase of healing. In addition, the β-lap-Lipo/ZBP/HEC formulation promoted local angiogenesis and reduced inflammation of the wound, demonstrating the potential of this original formulation of β-lap-Lipo/ZBP/HEC in cutaneous lesions therapy. To conclude, the developed nanocarriers are interesting approachs for intercepting the circulating melanoma cells, while liposomal formulations combining with original biopolymers have an interesting potential for wound healing applications.